2013
DOI: 10.2478/intox-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of non-steroidal anti-inflammatory drug use in hospitalized patients and perception of their risk

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) belong to the most widely prescribed and used pharmacological agents worldwide. Data gathered in the last decade show increased incidence of thrombotic events during NSAID administration. Analysis of NSAID usage and assessment of risk for development of cardiovascular adverse effects is needed for improving patient safety. For limiting the impact of adverse effects on the health of patients, NSAID users should be informed about the possible adverse effects and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
5
17
0
Order By: Relevance
“…We found seven studies (Biere-Rafi et al 2011;Chang et al 2010;Layton et al 2003a, b;Mangoni et al 2010b;Singh et al 2004;Varga et al 2013) that reported the effect of meloxicam exposure of any duration on the vascular system. Meloxicam was found to exhibit an elevated OR 0 (Table 3).…”
Section: Vascular Outcomesmentioning
confidence: 93%
See 2 more Smart Citations
“…We found seven studies (Biere-Rafi et al 2011;Chang et al 2010;Layton et al 2003a, b;Mangoni et al 2010b;Singh et al 2004;Varga et al 2013) that reported the effect of meloxicam exposure of any duration on the vascular system. Meloxicam was found to exhibit an elevated OR 0 (Table 3).…”
Section: Vascular Outcomesmentioning
confidence: 93%
“…We found 13 eligible studies with information on the concomitant ASA (Biere-Rafi et al 2011;Chang et al 2010;Garcia Rodriguez et al 2008;Huerta et al 2005;Lafrance and Miller 2012;Lapeyre-Mestre et al 2013;Layton et al 2003a, b;Mangoni et al 2010a, b;Schneider et al 2006;van Staa et al 2008;Varga et al 2013) (Table 4). In general, the use of ASA resulted in the widening of the 95 % CI around the calculated composite CV/renal risk estimates.…”
Section: Effect Of Asamentioning
confidence: 98%
See 1 more Smart Citation
“…Explaining the need to avoid duplicating NSAIDs was mentioned by only two interviewees, despite the potentially dangerous combination of prescription and non‐prescription NSAIDs being widespread . Few interviewees referred to the need to avoid NSAIDs or use them short term in older people or to exercise caution in patients with risk factors or concomitant drug use which could increase their chances of adverse events . The potential for acute effects on the kidney was only discussed in long‐term users.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Few interviewees referred to the need to avoid NSAIDs or use them short term in older people or to exercise caution in patients with risk factors or concomitant drug use which could increase their chances of adverse events. [3,4,12,13,20,[29][30][31] The potential for acute effects on the kidney [7] was only discussed in long-term users.…”
Section: Discussionmentioning
confidence: 99%